Analysis of the Effect of Website Implementation on Increasing Local MSME Sales: A Multiple Linear Regression Approach - Achmad Nawawi; Tufatul Adhan; Nely Nuriyah; Samso Supriyatna (Takaza Innovatix Labs Ltd., 2025)
MSMEs as the backbone of the Indonesian economy face the challenge of digital transformation in the Industrial Revolution 4.0 era, where many MSME websites in Tangerang City are not optimal so that sales stagnate despite significant investment. This study aims to prove the effect of website quality (X1) and digital marketing (X2) on increasing sales (Y) using a causal associative quantitative approach with multiple linear regression. The population includes MSMEs in Tangerang City, a sample of 50 purposive respondents who have had an active website for at least one year. The Likert 1-5 questionnaire instrument was analyzed using IBM SPSS 26 including validity-reliability tests, classical assumptions, and hypothesis tests. The results show a regression coefficient of Y = 12.450 + 0.452X1 + 0.385X2 with an adjusted R square of 0.685 (68.5%), both variables have a significant effect (sig. 0.000). The conclusion states that MSMEs need to optimize website UI/UX and SEO strategies for maximum sales conversion